Exceptional Engagement: Protocol I and a World United Against Terrorism - Newton, Michael (2009)
This article challenges the prevailing view that U.S. exceptionalism provides the strongest narrative for the U.S. rejection of Additional Protocol I to the 1949 Geneva Conventions. The United States chose not to adopt the Protocol in the face of intensive international criticism because of its policy conclusions that the text contained overly expansive provisions resulting from politicized pressure to accord protection to terrorists who elected to conduct hostile military operations outside the established legal framework. The United States concluded that the commingling of the regime criminalizing terrorist acts with the jus in bello rules of humanitarian law would be untenable and inappropriate. In effect, the U.S. concluded that key provisions of Protocol I actually undermine the core values that spawned the entire corpus of humanitarian law. Whether or not the U.S. position was completely accurate, it was far more than rejectionist unilateralism because it provided the impetus for subsequent reservations by other NA TO allies. More than two decades after the debates regarding Protocol I, the U.S. position provided the normative benchmark for the subsequent rejection of efforts by some states to shield terrorists from criminal accountability mechanisms required by multilateral terrorism treaties. This article demonstrates that the U.S. policy stance regarding Protocol I helped to prevent the commingling of the laws and customs of war in the context of the multilateralf ramework for responding to transnational terrorist acts in the aftermath of September 11. In hindsight, the exceptional U.S. position was emulated by other nations as they reacted to reservations designed to blur the distinctions between terrorists and privileged combatants. U.S. exceptionalism in actuality paved the way for sustained engagement that substantially shaped the international response to terrorist acts. This article suggests that reservations provide an important mechanism for states to engage in second-order dialogue over the true meaning and import of treaties, which in turn fosters the clarity and enforceability of the text